MENADŽMENT U SPORTU - Edita Kastratović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Practical use of management in sports goes back to the classical period, when gladiator fights accompanied by large number of spectators, were held. During 11th century The Olimpic games were opened with a magnificent ceremonies and included a lot of competition observed by a large crowd. Such large manifestations required: organised catering, promoters and numerous staff responsible for equipment and organisation of the whole event. Beside numerous definitions used in theory and practice, e.i. administration in sports, administration of athletes etc., the term ''management in sports'' is the only one that gives the global view of social reality and its full and the most precise explanation. It includes all activities and services in connection with: sport premises, equipment, location of event, hotels, trade of sport gear, physical culture, recreation and profesional sports.